2008
DOI: 10.1094/fg-2008-0818-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Bermudagrass Yield Response to Nitrogen and Potassium Fertilization in Northwest Arkansas

Abstract: Potassium performs a vital role in maintaining yield potential and stand persistence of bermudagrass (Cynodon dactylon L.) making proper fertilization critical for sustainable hay production. Our primary objective was to demonstrate how N and K fertilizer rates influence bermudagrass yield and soil‐test K across a four‐year period. Each year, N was applied at 180 and 300 lb/acre in three equal split applications in combination with K2O at 0 and 180 lb/acre. Potassium fertilization maintained soil‐test K betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…In 2006 and 2007, 90% ofthe maximum predicted yield of forage receiving 500 kg N ha"' yr"' would be produced by the application of 300 to 325 kg N ha" ' yr" ' as urea, 315 to 330 kg N ha" ' yr" ' as urea -(-NBPT, and 290 to 310 kg N ha"' yr"' as NH4NO3. Seay and Slaton (2008) estimated that 90% ofthe maximum bermudagrass yield would be produced with 400 kg N ha" '. Bermudagrass forage yields were not different among the inorganic N sotirces in 2006 and were always similar for urea and urea -(-NBPT (Table 6).…”
Section: Results and Discussion Season-total Forage Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006 and 2007, 90% ofthe maximum predicted yield of forage receiving 500 kg N ha"' yr"' would be produced by the application of 300 to 325 kg N ha" ' yr" ' as urea, 315 to 330 kg N ha" ' yr" ' as urea -(-NBPT, and 290 to 310 kg N ha"' yr"' as NH4NO3. Seay and Slaton (2008) estimated that 90% ofthe maximum bermudagrass yield would be produced with 400 kg N ha" '. Bermudagrass forage yields were not different among the inorganic N sotirces in 2006 and were always similar for urea and urea -(-NBPT (Table 6).…”
Section: Results and Discussion Season-total Forage Yieldmentioning
confidence: 99%
“…Seay and Slaton (2008) reported that 400 kg N ha"' yr"' would produce 90% relative forage yield of unirrigated bermudagrass in northwest Arkansas. To ensure accurate characterization of the N content and composition of the PPL, each year a 1-kg subsample of the bulk PPL was placed in a pla.stic bag, two or more suhsamples were removed, and each subsample was analyzed for total and inorganic N content as described ahove.…”
Section: Ammonia Volatilizationmentioning
confidence: 99%
“…During the winter after the second year of grazing, there was noticeable plant death in some pastures leaving open areas in the sward the following spring. Inadequate soil K levels have also been associated with poor persistence of bermudagrasses (Seay and Slaton, 2008). The decline in cover was most severe in pastures with the tallest SH.…”
Section: Postgraze Stubble Heightmentioning
confidence: 99%
“…Apparently, 2.24 Mg broiler litter/ha in 2011 provided sufficient K (∼68 kg K 2 O/ha) for bermudagrass growth requirement, but did not provide cultural control of the disease complex caused by species of Bipolaris , Curvularia , and Exserohilum . In addition to K, broiler litter provides carbon and other nutrients important to bermudagrass growth (4,13,18).…”
Section: Disease Severity Estimatesmentioning
confidence: 99%
“…], a warm‐season perennial forage, has long been used for hay and pasture by beef and dairy cattle producers in Mississippi. Because bermudagrass is responsive to N and requires comparable amounts of K for optimal growth, its yield potential is highest when N and K availability are balanced (16,18). Broiler litter, a mixture of poultry manure, wasted feed, and bedding materials, has an N‐P 2 O 5 ‐K 2 O fertilizer equivalent of approximately 2.9‐1.5‐3.0 with 19% moisture content (4).…”
Section: Introductionmentioning
confidence: 99%